2020
DOI: 10.1080/23311932.2020.1785778
|View full text |Cite
|
Sign up to set email alerts
|

Improved legume fallows: Influence on nitrogen and microbial dynamics, and maize (Zea maysL) grain yield in sub-humid zone of West Africa

Abstract: This study tested the effect of four improved fallow legumes; Leucaena leucophala, Cajanus cajan, Albizia lebbeck and Moringa oleifera (for 1 and 2 year period) on soil nitrogen, microbial dynamics and maize grain yield in the sub-humid zone of Ghana. The study was conducted at the University for Development Studies experimental station, at latitude 9° 25ꞌ N, longitude 0° 58 ꞌ W and at 183 m asl. The layout of the experiment was a randomized complete block design (RCBD) with four replications. The pattern of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Moringa has been grown in a variety of agricultural systems ranging from horticulture (monocropping or intercropping) [ 256 , 342 ] to agroforestry [ 105 , 115 , 118 , 119 , 120 , 141 , 191 , 197 , 202 , 216 , 272 , 383 , 385 , 389 , 407 ]. It has been indicated as suitable for intercropping with vegetables, fruit trees, and medicinal and aromatic plants in South Africa [ 364 ] and legumes (cowpea, jack bean, lablab, and pigeon pea) in South Africa [ 339 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moringa has been grown in a variety of agricultural systems ranging from horticulture (monocropping or intercropping) [ 256 , 342 ] to agroforestry [ 105 , 115 , 118 , 119 , 120 , 141 , 191 , 197 , 202 , 216 , 272 , 383 , 385 , 389 , 407 ]. It has been indicated as suitable for intercropping with vegetables, fruit trees, and medicinal and aromatic plants in South Africa [ 364 ] and legumes (cowpea, jack bean, lablab, and pigeon pea) in South Africa [ 339 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been indicated as suitable for intercropping with vegetables, fruit trees, and medicinal and aromatic plants in South Africa [ 364 ] and legumes (cowpea, jack bean, lablab, and pigeon pea) in South Africa [ 339 ]. As for agroforestry, moringa has been investigated in Benin [ 118 , 119 , 120 ], Cameroon [ 141 ], Ethiopia [ 105 , 191 , 197 ], Ghana [ 202 , 216 ], Kenya [ 105 ], Nigeria [ 272 ], Tanzania [ 383 ], Togo [ 385 ], and Tunisia [ 389 ]. In this respect, Boumenjel et al [ 389 ] concluded that “ Moringa represent a promising species as an ecological solution for use in agroforestry systems, able to minimize the negative effects of drought and to rehabilitate and enhance the soil of arid zones ” (p. 823).…”
Section: Resultsmentioning
confidence: 99%
“…to Gnahoua et al (2014). The litter produced by A. lebbeck was thus assumed to decompose faster than that produced by the other species, resulting in mass losses of 60-70% annually (Singh et al, 2004;Ochire-Boadu et al, 2020). Cacao leaves, which have lower annual decomposition rates, lose 30-40% of their mass (Yao et al, 2021;Bai et al, 2022).…”
Section: Discussionmentioning
confidence: 99%